2021
DOI: 10.3390/catal11020250
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction: From Basic Science to deNOx Applications

Abstract: The combustion of coal, petroleum and biofuel for energy generation has resulted in unprecedented benefits to the prosperity of our modern society and will continue to do so in the future. However, rapid global climate changes, especially frequent extreme weather conditions that we have witnessed in the past two decades, remind us how fragile our planet is, and how important sustainable development is for future generations. The advancement of sciences and technologies for environmental protection, such as wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This catalytic process is based on the reaction between nitrogen oxide and ammonia in the presence of oxygen and it yields molecular nitrogen and water vapor. The technology was developed in the 1970s in Japan and has become widespread around the world [5,6]. In recent years, the most common commercial catalytic system of NH 3 -SCR is V 2 O 5 -TiO 2 promoted with MoO 3 or WO 3 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This catalytic process is based on the reaction between nitrogen oxide and ammonia in the presence of oxygen and it yields molecular nitrogen and water vapor. The technology was developed in the 1970s in Japan and has become widespread around the world [5,6]. In recent years, the most common commercial catalytic system of NH 3 -SCR is V 2 O 5 -TiO 2 promoted with MoO 3 or WO 3 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [11] also demonstrated that the co-combustions of textile dyeing sludge and waste tea reduced SO 2 emission through thermogravimetric coupled with mass spectrometry (TG-MS) analysis. It is essential to quantify the release of gaseous pollutants in the co-combustion process of sewage sludge and gasification fine slag residual carbon, which can provide important inspiration for the control of pollutants in industrial burner in the future [25][26][27].…”
Section: Introductionmentioning
confidence: 99%